Valikoima runoelmia - Heine, Heinrich, 1797-1856; Juva, Valter, 1865-1922 (Salt Lake City, UT : Project Gutenberg, 2009)
"Valikoima runoelmia" by Heinrich Heine is a collection of selected poems written in the early 20th century, translated into Finnish by Valter Juva. This anthology draws upon various works of the renowned German poet, encompassing themes of love, longing, and melancholy, offering a glimpse into Heine's lyrical exploration of human emotions. The opening of this collection serves as an introduction to Heinrich Heine's poetry through the translator's notes, highlighting the legacy of his works and their translations into Finnish. It discusses the significance of Heine's verses and the selections chosen for this anthology, which feature poems from his notable collections such as "Buch der Lieder" and "Neue Gedichte." The initial poems reflect a blend of romantic sentiments intertwined with feelings of sadness, deftly capturing the essence of existence and the pains of unrequited love. The preface sets the stage for the deeply personal and evocative nature of the poetry that follows, inviting readers to engage with Heine's rich emotional landscape. (This is an automatically generated summary.)
Release date is 2009-08-16
Produced by Matti Järvinen and Distributed Proofreaders Europe
Keywords: Poetry